Prevention of alcohol and other drug use using motivational interviewing among young adults in the Ukraine - Polshkova, Svitlana; Voloshina, Diana; Cunningham, Rebecca; Zucker, Robert; Walton, Maureen (Psychosomatic Medicine and General Practice, 2016)
Background. World Health Organization data show alarming rates of alcohol consumption among those aged 15 and older in Ukraine. This study examined the feasibility and initial efficacy of a brief intervention to reduce risky drinking among adults (age between 18-25) in Ukraine. Methods. Adults were screened for risky drinking with the Alcohol Use Disorders Identification Test (AUDIT-C). Those with AUDIT-C score (>5) were enrolled in the study: 59 participants from the hospital setting (mean age = 22.6 (2.1), 55.9% male) and 61 participants from the university setting (mean age = 20.1(2.3), 55.7% male). After self-administering a computerized baseline assessment, participants were randomized to receive an in-person brief intervention by telephone or to a control condition; participants underwent a computerized follow-up at 3 months. Results. Regression analyses for prediction of alcohol outcomes (alcohol consumption and consequences) were conducted separately for each setting; models were controlled for baseline alcohol levels and assigned condition (brief intervention or control). In both settings, the brief intervention group showed significantly less alcohol consumption and consequences at 3-months as compared to the control group (p<.001); however, the groups did not significantly differ on other drug use (DAST-10 score). Conclusion. Findings suggest that brief motivational interventions are promising for reducing risky drinking among emerging adults in the Ukraine in both inpatient hospital and university settings. Future studies are needed to replicate these findings and extend these effects to reduce other drug use among young people in the Ukraine.